Substituted azafluorenones: access from dihalogeno diaryl ketones by palladium-catalyzed auto-tandem processes and evaluation of their antibacterial, antifungal, antimalarial and antiproliferative activities. Issue 6 (11th February 2016) - Marquise, Nada; Chevallier, Floris; Nassar, Ekhlas; Frédérich, Michel; Ledoux, Allison; Halauko, Yury S.; Ivashkevich, Oleg A.; Matulis, Vadim E.; Roisnel, Thierry; Dorcet, Vincent; Mongin, Florence
Abstract: Substituted azafluorenones were synthesized from dihalogeno diaryl ketones under palladium catalysis by combining, in auto-tandem processes, Suzuki coupling and intramolecular arylation reactions. Different dihalogenated diaryl ketones, prepared by sequential deprotocupration-aroylation, were identified as suitable substrates to this purpose. Conditions were identified to allow successful syntheses of several 6-/7-arylated 4-azafluorenones, 1-substituted 4-azafluorenones, 2-phenyl-3-azafluorenone, and 4-phenyl-3-azafluorenone from 3-(bromobenzoyl)-2-chloropyridines, 3-benzoyl-4-bromo-2-chloropyridines, 4-benzoyl-2, 5-dichloropyridine, and 4-benzoyl-2, 3-dichloropyridine, respectively. Some of the synthesized compounds exhibit interesting biological properties. Graphical abstract: